BEDA PENGARUH PEMBERIAN LATIHAN KNEE TUCK JUMP DENGAN SKIPPING TERHADAP PERUBAHAN DAYA LEDAK OTOT TUNGKAI PEMAIN BOLA BASKET DI CLUB FURRY BALL MAKASSAR - Andi Halimah; Muhammad Gibran Tabara; Anshar Anshar (Media Fisioterapi Politeknik Kesehatan Makassar, 2021)
Background: Explosive power or power is a combination of two biomotoric elements, namely speed and strength combined to produce power. To increase power, the training provided must pay attention to the elements of speed and strength in order to get maximum results.Methods: This study was a quasi-experimental study using a two-group pre test and post test design, aiming to determine the difference in the effect of knee tuck jump training and skipping on changes in leg muscle explosive power of basketball players at furry ball clubs Makassar. This research was conducted at the Makassar furry ball club with a sample of 12 people who fit the inclusion criteria, divided randomly into 2 groups, namely the treatment group 1 which was given knee tuck jump training and the treatment group 2 which was given skipping practice. The measuring tool used is the vertical jump test.Results: Based on the Wilcoxon test analysis in treatment group 1 and treatment group 2, a value of (.028) was obtained (.028) p <0.05, which means that there was a significant effect in treatment group 1 and treatment group 2 on increasing the explosive power of the limb muscles of basketball players in the club Makassar furry ball. The results of the Mann-Whitney test obtained a value of (.179) p> 0.05 which means that there was no significant difference between the two sample groups, but seen from the mean value it showed that the knee tuck jump exercise resulted in an increase in muscle explosive power that was greater than skipping exercise.Conclusion: It can be concluded that there is no significant difference in effect between giving knee tuck jump training and skipping to changes in leg muscle explosive power in basketball players at the Makassar furry ball club. Keywords: Muscle explosive power, Knee Tuck Jump, Skipping, Vertical Jump Test